Nanostructured lipid carriers mediated transdermal delivery of trandolapril as an impeccable therapeutic approach against hypertension: Development, characterization and in vivo evaluation - Ramankit Jaiswal; Rita Wadetwar (Elsevier, 2023)
The study aimed to design trandolapril-embedded nanostructured lipid carriers (NLCs) transdermal patch and evaluate its in vitro drug permeation, bioavailability and pharmacokinetics. Trandolapril, a poorly soluble drug with antihypertensive activity, was used and investigated in the development of NLCs formulations. High-pressure homogenization was used to develop the drug-loaded NLCs formulations, which were then optimized utilizing the box Behnken design. The optimized batch of NLCs formulation includes oleic acid as liquid lipid, solid lipid as Precirol ATO 5 and surfactant poloxamer 188. The developed NLCs had a mean particle size of 82.48 ± 2.16 nm and a zeta potential of - 20.6 ± 2.18 mV. Tailored NLCs were loaded into the transdermal patch and molded using a solvent casting technique and evaluated for thickness, moisture content, weight variation and folding endurance. Furthermore, the in vitro permeation of trandolapril from the transdermal patch was measured using Franz diffusion cells and compared to a pure trandolapril patch. When compared to an oral trandolapril suspension, in vivo pharmacokinetic studies with an NLCs-loaded transdermal patch reveal an increase in maximum plasma concentration (Cmax) and concentration-time curve (AUC). These findings showed that trandolapril-NLCs might be a viable transdermal delivery option.